Sports criminology : a critical criminology of sport and games - Groombridge, Nic (New horizons in criminology., 2016)
This is the first book to provide a critical criminological perspective on sport and the connections between sport and crime. It draws on the interdisciplinary nature of criminology and incorporates emerging perspectives like social harm, gender and sexuality, and green criminology. Written from an international perspective, it covers topics including sports scandals and the possibility of crime prevention through sport. American football, boxing, soccer and sumo are all examined. The book considers both sports law and the sociology of sport and will be essential reading for students and academics in these fields.